RPS9M, a Mitochondrial Ribosomal Protein, Is Essential for Central Cell Maturation and Endosperm Development in Arabidopsis - Lu, Changqing; Yu, Feng; Tian, Lianfu; Huang, Xiaoying; Tan, Hong; Xie, Zijing; Hao, Xiaohua; Li, Dongping; Luan, Sheng; Chen, Liangbi (Frontiers in Plant Science, 2017)
During double fertilization of angiosperms, the central cell of the female gametophyte fuses with a sperm cell to produce the endosperm, a storage tissue that nourishes the developing embryo within the seed. Although many genetic mutants defective in female gametophytic functions have been characterized, the molecular mechanisms controlling the specification and differentiation of the central cell are still not fully understood. Here, we report a mitochondrial ribosomal protein, RPS9M, is required for central cell maturation. RPS9M was highly expressed in the male and female gametophytes before and after double fertilization. The female gametophytes were defective in the rps9m mutant specifically concerning maturation of central cells. The morphological defects include unfused polar nuclei and smaller central vacuole in central cells. In addition, embryo initiation and early endosperm development were also severely affected in rps9m female gametophytes even after fertilized with wild-type pollens. The RPS9M can interact with ANK6, an ankyrin-repeat protein in mitochondria previously reported to be required for fertilization. The expression pattern and mutant phenotype of RPS9M are similar to those of ANK6 as well, suggesting that RPS9M may work together with ANK6 in controlling female gametophyte development, possibly by regulating the expression of some mitochondrial proteins.